Usulan Penentuan Strategi Pendistribusian yang Optimal (Studi Kasus : PT. X) - Trifenaus Prabu Hidayat; Anastasia Kristinawati (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2014)
The purposes of this research is to analyze the optimal distribution system at PT. X. There are three alternatifs given. The method used is saving matrix method and Knapsack using distance and time data. This research is considered the traffic conditions so the distance matrix is transformed into time matrix. The result show the distribution route and sequence of optimal methods. Distribution route is obtained using Farthest Insert, Nearest Insert and Nearest Neighbor. The sequence of methods is placed saving matrix method at first and then Knapsack or vice versa. After this, the distribution cost is calculated for three alternatifs given. This cost calculation is considered pinalty cost which is the value of opportunity cost when truck is not fully used. The results of cost calcutation show, when considered penalty cost, the best alternatif is alternatifs three that deliveries all consumer demand with freight forwarding services. However, this penalty charge is not real value (not spending money) so the company does not consider the cost of this penalty. When calculating cost without penalty cost, the best alternatif is alternatif one that deliveries all consumer demand with the company’s truck. In the first alternatif, the best method is saving matrix distance – knapsack. This method aims to select nearby consumers then optimize the distribution fleet.